PENERAPAN SOCIAL MEDIA MARKETING DALAM MENINGKATKAN ENGAGEMENT TIKTOK PADA PT DOYAN MITRA SEJAHTERA - Rachel Octavia Qurrota Ayuni; Sukaris (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the implementation of Social Media Marketing in increasing engagement on the TikTok account @doyanayam. The novelty of this research lies in its focus on the application of Social Media Marketing within a franchise-based food and beverage company by utilizing TikTok account performance data as the basis for analysis. This study employed a qualitative research method with a descriptive approach. Data were collected through interviews with Sintia Dwi Rahmawati as the Social Media Specialist of PT Doyan Mitra Sejahtera, observations of the activities on the @doyanayam TikTok account, and documentation in the form of the TikTok Social Media Report (SMR) for August 2025. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of Social Media Marketing was carried out through creative content creation, the utilization of TikTok trends, the use of relevant hashtags, and active interaction with the audience. These strategies successfully increased user engagement, as reflected in the growth of views, likes, comments, and shares on the published content. This study concludes that consistent and audience-oriented Social Media Marketing strategies can effectively enhance engagement on TikTok. The findings are expected to provide practical insights for businesses, particularly in the food and beverage industry, in optimizing TikTok as an effective digital marketing platform.